2016
DOI: 10.14260/jemds/2016/1586
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Versus Interrupted Sutures for Episiotomy Wound Repair

Abstract: BACKGROUNDMost of the women undergoing vaginal deliveries experience perineal trauma. Considering the high prevalence of maternal morbidity in relation to perineal trauma after delivery, the need for repair and local pain, this study was conducted to present the best method of episiotomy repair with minimum complications.The aim of this study is to compare continuous with interrupted suturing technique for the procedure of Episiotomy. Setting and design, a prospective comparative study was carried out in the D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…A study done in 2017 at Dharmapuri Medical College compared catgut with absorbable synthetic suture material and found that the polyglactin group had superior wound healing with nil or zero percent wound dehiscence on PND 7 compared to 15% in the catgut group, which is similar with our sudy [9] . In a study performed in Maharashtra comparing two methods of suturing and wound repair in India's rural population, the continuous procedure was found to be superior to the intermittent technique, with 58 percent of the continuous suturing group experiencing pain compared to 76 percent of the intermittent group experiencing pain [12] . These findings are consistent with all prior research, which has found that wound healing is better with vicryl rapide than with chromic catgut.…”
Section: Discussionmentioning
confidence: 99%
“…A study done in 2017 at Dharmapuri Medical College compared catgut with absorbable synthetic suture material and found that the polyglactin group had superior wound healing with nil or zero percent wound dehiscence on PND 7 compared to 15% in the catgut group, which is similar with our sudy [9] . In a study performed in Maharashtra comparing two methods of suturing and wound repair in India's rural population, the continuous procedure was found to be superior to the intermittent technique, with 58 percent of the continuous suturing group experiencing pain compared to 76 percent of the intermittent group experiencing pain [12] . These findings are consistent with all prior research, which has found that wound healing is better with vicryl rapide than with chromic catgut.…”
Section: Discussionmentioning
confidence: 99%